Morphology and Functional Behavior of Polyacrylamide Hydrogels Reinforced with Sustainable Montmorillonite Nanoclay - I. Adeleke, Abayomi; R. Sanders, Jonathan; Arce, Pedro E. (New Environmentally-Friendly Materials, 2025)
Polyacrylamide (PAAM) hydrogels are widely used in electrophoretic separations of proteins, deoxyribonucleic acid (DNA), and cells due to their high resolving power, optical and ultraviolet (UV) transparency, electro-neutrality, and tunable pore structure. Incorporation of nanomaterials into PAAM gels has been proposed as a strategy to further tailor gel microstructure and transport properties. In this study, sodium montmorillonite (Na-MMT) nanoplatelets, a naturally occurring nanoclay with an average diameter of 400 nm and an aspect ratio of 150, were incorporated into PAAM gels to form nanocomposite hydrogels, and their effects on protein mobility were systematically investigated. Native polyacrylamide gel electrophoresis revealed that Na-MMT incorporation consistently reduced protein mobility relative to pure PAAM gels. To elucidate the origin of this behavior, rheological measurements and scanning electron microscopy (SEM) were employed. Rheological analysis showed that pure PAAM gels exhibited greater elasticity than nanocomposite gels, attributed to disruption of the polymer network by nanoplatelet incorporation and extended sonication during sample preparation. SEM image analysis further revealed the absence of well-defined matrix cells in the nanocomposite gels. Instead, osmotic-pressure-driven nanoparticle aggregation produced dense, poorly interconnected nanopores that impeded effective protein transport. These structural changes led to reduced electrophoretic mobility and separation efficiency. Overall, the findings demonstrate that PAAM–bentonite nanocomposite hydrogels exhibit inherent microstructural limitations for electrophoretic applications, emphasizing the need for precise control of nanoparticle dispersion and gel architecture in the design of nanocomposite separation media.